Effectiveness evaluation and field application of CO2-viscoelastic fluid synergistic flooding in low-permeability tight reservoirs - TANG Ruijia, CHEN Longlong, XIE Xuqiang, ZHAO Cong, WANG Beilei, JIANG Shaojing (Youqicang pingjia yu kaifa)
CO2 sweep efficiency and gas channeling are key factors restricting the effectiveness of CO2 flooding in low-permeability tight reservoirs. To address the technical issues of low sweep efficiency and gas susceptibility to channeling in CO2 flooding, a viscoelastic fluid system (CMS) was proposed to improve CO2 flooding in low-permeability tight reservoirs. A systematic study was conducted on the viscoelasticity, interfacial activity, injectivity, plugging performance, and oil displacement performance of CMS under oil reservoir conditions. The synergistic flooding performance of CO2-CMS was explored, and field trials were carried out. Experimental results demonstrated that at reservoir temperatures ranging from 30-80 ℃, CMS with a mass fraction of 0.5% showed certain viscoelasticity, with elasticity as the dominant characteristic, and both viscosity and elasticity decreased as temperature increased. At an oil reservoir temperature of 45 ℃, the viscosity of CMS was 3.27 mPa·s, and it exhibited strong elasticity. Furthermore, CMS could effectively reduce the oil-water interfacial tension to 2.68×10-2 mN/m. After core samples were immersed in the CO2-CMS system, the water-phase contact angle decreased to 8.75°, indicating enhanced hydrophilicity. The CO2-CMS system demonstrated good injectability in low-permeability tight cores, with smaller slug sizes yielding better injection performance. In long-core displacement experiments, using a 0.3 PV slug of CMS followed by CO2 flooding increased the recovery rate by up to 27.79%. In double-tube parallel core displacement experiments, alternating CMS and CO2 proved most effective, as it successfully sealed the high-permeability cores and mobilized low-permeability cores, resulting in a 26.28% increase in recovery. Field trial data from well groups indicated that after applying CMS, the overall liquid and oil production increased, and the CO2 volume fraction in gas-channeling wells significantly decreased. This research provides new technical insights and practical solutions for improving the efficiency of CO2 flooding in low-permeability tight reservoirs.